Oral interaction as per the theory of courtesy - Zuluaga Gómez, Francisco Octavio (Íkala, Revista de Lenguaje y Cultura, 2004)
This article analyses verbal interaction from the point of view of politeness theory. Politeness is characterized according to the pioneers´ approaches to this subject (Lakoff, Fraser, Leech, Haverkate, Brown and Levinson). The analysis then focuses on Brown and Levinson´s model of politeness theory, based on the concept of face. In order to explain the linguistic realization of politeness, examples are taken from both authentic texts and dialogues of novels. Received: 20-11-03 /Accepted: 16-09-04 How to reference this article: Zuluaga Gómez, F. O. (2004). La interacción verbal vista desde la teoría de la cortesía. Íkala. 9 (1), pp. 389 – 421